The Influence of Work Discipline and Work Motivation on Organizational Strategy Mediated by Work Supervision at BPJS Employment in Medan Raya - Fitriyani Hasibuan; Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
BPJS Employment has functions and responsibilities such as, conducting and receiving registration for BPJS participants, collecting and collecting contributions from participants and employers, receiving contribution assistance from the government, managing social security funds for the benefit of participants, collecting and managing data on participants in the social security program, providing benefits and financing health services in accordance with the provisions of the social security program, and also responsible for providing information about implementation of social security programs to participants and the community. This study aims to see the Influence of Work Discipline and Work Motivation on Organizational Strategy Mediated by Work Supervision at Bpjs Employment in Medan Raya, the results of this study are as follows; Work Discipline had a positive and significant effect on Work Supervision with the original sample value of 0.646 and p values of 0.000. Work Discipline had a positive and significant effect on Organizational Strategy with the original sample value of 0.348 and p values of 0.000. Work Motivation had a positive and significant effect on Work Supervision with the original sample value of 0.298 and p values of 0.000. Work Motivation had a non-significant positive effect on Organizational Strategy with the original sample value of 0.090 and p values of 0.209. Work Supervision had a positive and significant effect on the Organizational Strategy with the original sample value of 0.508 and p values of 0.000. Work Discipline has a positive and significant effect on Organizational Strategy through Work Supervision with an original sample value of 0.328 and p values of 0.000. Work Motivation has a positive and significant effect on Organizational Strategy through Work Supervision with an original sample value of 0.151 and p values of 0.000.